PRODUKSI DAN ANALISIS KELAYAKAN FINANSIAL AGROINDUSTRI BIOETANOL BATANG SAGU DI KABUPATEN MIMIKA, PAPUA - Tentri Yera Idqa Ridmaningrum; Meika Syahbana Rusli; Dwi Setyaningsih (AGROINTEK, 2020)
The utilization of sago as a product which have higher value have not used maximally yet. Sago (Metroxylon spp.) is one of original plant from Indonesia which could be used as raw material for bioethanol. The objectives of the study were to analyze production of bioethanol with the variation of yeast Saccharomyces cereviceae concentration added (7%, 12%, 17%), fermentation time were (5 days and 7 days) and analysis of the financial feasibility industry from sago palm. The methods of the study analyze the financial feasibility by NPV, IRR, Net B/C, PBP, and sensitivity analysis. The result showed that fermentatiom time 7 days and yeast consentration 12% is the optimum tretments producted bioethanol from sago which result consentration 3,05% (v/v). The financial feasibility are Net Present Value is positive amounted Rp. 125 859 652 242, Internal Rate of Return of 17%, Net B/C ratio by 1,53, Payback Period for 6 years, and Sensitivity analysis showed that the 12% increase in raw material and 8% decrease in selling price, effect on the viability of the project. From the above considerations investment criteria, indicates that the business of bioethanol based on sago is feasible to run.